The shape of things to come - Barker, Melinda; Games, Martin Hughes (Bristol : BBC-TV Production [production company] ; London : BBC Education & Training [distributor], 1994)
Describe on the design shape by the nature
Produced by BBC-TV Production in association with Lionheart Television International
Film editor, Martin Elsbury
Narrator: Richard Jobson
Keywords: Shapers